2017
DOI: 10.1063/1.5003397
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance originated from charge-spin conversion in ferromagnet

Abstract: Transverse magnetoresistance in a ferromagnetic/nonmagnetic/ferromagnetic trilayer originated from charge-spin conversion by anomalous Hall effect is investigated theoretically. Solving the spin diffusion equation in bulk and using the spin-dependent Landauer formula at the ferromagnetic/nonmagnetic interface, an analytical formula of the transverse resistivity is obtained. The charge-spin conversion by the anomalous Hall effect contributes to the magnetoresistance in a manner proportional to the square of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…However, the spin direction of the spin accumulation generated via the SHE is fixed, parallel to the interface, depending only on the direction of the charge current through the heavy nonmagnetic metal [Figure a]. Alternatively, the anomalous Hall effect in ferromagnetic metals can be used as a tunable source of transverse spin current, as has been theoretically predicted and recently demonstrated experimentally. We call this phenomenon the anomalous spin Hall effect (ASHE), which generates a spin accumulation oriented parallel to the ferromagnet’s magnetization [Figure b–d]. In principle, the ASHE provides a novel way of electrically injecting and detecting a spin accumulation with out-of-plane components, which can be controlled by manipulating the ferromagnet’s magnetization.…”
mentioning
confidence: 99%
“…However, the spin direction of the spin accumulation generated via the SHE is fixed, parallel to the interface, depending only on the direction of the charge current through the heavy nonmagnetic metal [Figure a]. Alternatively, the anomalous Hall effect in ferromagnetic metals can be used as a tunable source of transverse spin current, as has been theoretically predicted and recently demonstrated experimentally. We call this phenomenon the anomalous spin Hall effect (ASHE), which generates a spin accumulation oriented parallel to the ferromagnet’s magnetization [Figure b–d]. In principle, the ASHE provides a novel way of electrically injecting and detecting a spin accumulation with out-of-plane components, which can be controlled by manipulating the ferromagnet’s magnetization.…”
mentioning
confidence: 99%
“…14 Due to the strong exchange coupling, the spin polarization of the transverse spin current is believed to be aligned with the local magnetization direction (or longitudinal spin polarization). Although this provides a convenient way to control the spin polarization direction using an external field, [15][16][17][18][19][20] it also means that the AHE-generated non-equilibrium spins in a single layer FM are unable to exert a torque on its own magnetization. 15,16 Recently, we have demonstrated that a different scenario emerges in the vicinity of the surface of a thin FeMn layer, particularly within the range of spin relaxation lengths.…”
mentioning
confidence: 99%
“…Miao et al realized the IAHE (but termed it the ISHE) by using a thermal gradient in the ferromagnetic insulator YIG (Yttrium Iron Garnet) to inject a spin current into the ferromagnetic alloy permalloy (Py=Ni 80 Fe 20 ) and produced a transverse charge current with an efficiency comparable to, albeit smaller than, that of Pt [122]. Subsequent experiments [36,39,[123][124][125][126][127][128][129][130][131][132][133][134][135] and theoretical investigations [38,42,121,136,137] confirm their observation that for Py and other 3d ferromagnetic materials spin Hall effects are comparable in magnitude to those observed in 5d materials leaving one to wonder if the absolute value of the SOC parameter ξ alone determines the size of Θ sH . The hopping between orbitals on neighbouring atoms that is measured by the bandwidth W reduces the effective spin orbit splitting by mixing the split states [138,139].…”
Section: 1(d)mentioning
confidence: 99%